Does Jealousy of Others Make Us Happy? - Svatoš, Jiří; Stroukal, Dominik, 1987-; Špecián, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
The relative income is often cited as a reason why happiness of nations does not grow in time with growing GDP. The study replicates the methodology of several different researchers from basic scatterplots, standard OLS and ordered probit models to hierarchical linear multilevel models (HLM). The results provide evidence that the happiness is actually rising with the growing GDP, although slowly and with the GDP measured in logarithm. On the contrary, the relevance of relative income to happiness is ambiguous through all the proposed models. Furthermore, the individual characteristics like marital status or employment status are proved to explain the differences in happiness much better than income. Finally it is shown that income has similar effects on different measurements of subjective well-being (health, happiness and emotional well-being).
Vedoucí práce: Dominik Stroukal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses